2010
DOI: 10.1167/iovs.09-4667
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of the 2- to 4-Month-Old Human Infant Accommodation System

Abstract: In infants 2 to 4 months of age, the developing visual system compensates for small changes in defocus relative to the typical amounts of hyperopic refractive error found at that age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
(58 reference statements)
1
15
1
Order By: Relevance
“…Additional, previously unreported, vergence data from a study conducted by Wang and Candy (2010) are also shown in Figure 4. This experiment was performed in a largely similar way on 2- to 4-month-old infants.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Additional, previously unreported, vergence data from a study conducted by Wang and Candy (2010) are also shown in Figure 4. This experiment was performed in a largely similar way on 2- to 4-month-old infants.…”
Section: Resultsmentioning
confidence: 92%
“…Signal and noise vergence amplitudes for adults (top, red), 5- to 10-week-olds (middle, blue), and 12- to 20-week-olds from Wang and Candy (2010; bottom, green). Filled symbols represent the signal response at 0.1 Hz while the stimulus was moving.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations